Efektivitas Terapi Konseling Trauma-Focused pada Anak Narapidana di LPKA Tomohon - Fharil Yosafat Panungkelan; Blessthinky S Nender; Frisilia M Bolung (STIE AMKOP, 2023)
Juvenile delinquents are at risk of experiencing psychological trauma that negatively impacts their mental health and future. However, the treatments given to juvenile delinquents in Indonesia are still limited in efficacy. Trauma-focused counseling (TFC) has the potential to help them overcome trauma issues. This study aims to explore the implementation and benefits of TFC for juvenile delinquents. Research methods: A qualitative case study approach was used. The research subjects were 5 juvenile delinquents in the Tomohon Juvenile Detention Center who underwent TFC. Data was collected through in-depth interviews, observations and document studies. Data analysis was carried out inductively using the Miles and Huberman models. Results: TFC provenly provides effective coping, more positive self-interpretation and future outlook, as well as supports the emotional well-being of subjects. There has been a decrease in negative symptoms and destructive behavior due to trauma. Conclusion: TFC has great potential to be implemented for juvenile delinquents in Indonesia for rehabilitation, social reintegration and child protection purposes. Keywords: trauma-focused counseling, juvenile delinquents, trauma therapy, rehabilitation